Pharmalink : UiTM x UNHAS 2025 - Azizi, Fatin Izyani; Khairul Hamidy, Nuraleeya Haziqah Putri; Ibrahim, Norkasihan; Jahidin, Aisyah Hasyila (2025)
In September 2025, six students from the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM), embarked on a six-day student exchange programme at Universitas Hasanuddin (UNHAS) in Makassar, Indonesia. The programme offered a rich mix of activities, from hands- on laboratory sessions to leadership development workshops. During their stay, the students explored laboratory techniques and gained firsthand insight into the organisational practices at UNHAS, inspiring ideas that could enhance UiTM’s Faculty of Pharmacy, particularly in student engagement and organisational structure.